2022
DOI: 10.1155/2022/7372202
|View full text |Cite
|
Sign up to set email alerts
|

FBXL16 Promotes Endometrial Progesterone Resistance via PP2AB55α/Cyclin D1 Axis in Ishikawa

Abstract: Background. F-box proteins are essential components of the E3 ubiquitin ligases which are involved in the regulation of almost all life activities such as cell cycle, proliferation, and apoptosis, which have become an important research and drug target. However, there are few studies on F-box and leucine-rich repeat protein 16 (FBXL16) in endometrial carcinoma. Methods. Clinical samples were collected for determining the correlation between FBXL16 and endometrial carcinoma. Cells were screened and established … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 29 publications
0
1
0
Order By: Relevance
“…Through their F-box domains, F-box proteins usually form an SCF (SKP1-CUL1-F-box) complex to constitute an active E3 ubiquitin ligase in which the F-box protein recruits substrates for protein ubiquitination [9,10]. While FBXL16 did not show detectable interaction with CUL1 and may not form an active E3 ligase [11,12], recent studies have demonstrated that FBXL16 is involved in regulating the ubiquitination and stability of oncoproteins, such as MYC, SRC3, CYCLIN D1, and HIF1 alpha [13][14][15][16]. By upregulating MYC stability, FBXL16 promotes cancer cell growth and migration [13].…”
Section: Introductionmentioning
confidence: 99%
“…Through their F-box domains, F-box proteins usually form an SCF (SKP1-CUL1-F-box) complex to constitute an active E3 ubiquitin ligase in which the F-box protein recruits substrates for protein ubiquitination [9,10]. While FBXL16 did not show detectable interaction with CUL1 and may not form an active E3 ligase [11,12], recent studies have demonstrated that FBXL16 is involved in regulating the ubiquitination and stability of oncoproteins, such as MYC, SRC3, CYCLIN D1, and HIF1 alpha [13][14][15][16]. By upregulating MYC stability, FBXL16 promotes cancer cell growth and migration [13].…”
Section: Introductionmentioning
confidence: 99%